Etching reactions of C2H5I on GaAs(100) - Singh, N; Bolzan, A; Foord, J; Wright, H (1998)
The surface reactions of ethyl iodide on GaAs(100) have been studied using Auger Electron Spectroscopy (AES), Low Energy Electron Diffraction (LEED) and Thermal Desorption Spectroscopy in conjunction with isotope scrambling experiments with deuterium. Ethyl iodide was found to adsorb dissociatively at room temperature, to form chemisorbed ethyl and iodine species. Recombinative desorption of molecular ethyl iodide competes with the further surface reactions of ethyl and iodine. The ethyl species undergoes β-hydride elimination reaction to form ethene, ethane and hydrogen, which all desorb into the gas phase. Iodine selectively etches surface gallium atoms as GaI, which subsequently desorbs at 520 K, and this species was the major halide etch product formed for all exposures of ethyl iodide. HI desorption forms a minor channel for the removal of surface iodine. As2 desorption occurs from arsenic-enriched surfaces for temperatures greater than 600 K, and it is postulated that at high surface concentrations of chemisorbed arsenic dimers, As4 desorption must also become feasible. LEED and AES studies show that repetitive exposure of the gallium-rich GaAs(100)-(4 × 1) surface with ethyl iodide followed by annealing to 700 K gives rise to the arsenicrich c(4 × 4) structure, and this observation is consistent with the thermal desorption data. A reaction scheme is proposed to account for the observed desorption products, and the etching behaviour of ethyl iodide is discussed in the light of the reaction mechanism elucidated. © 1998 Published by Elsevier Science B.V. All rights reserved.